In vitro and in vivo anti-biofilm activity of pyran derivative against Staphylococcus aureus and Pseudomonas aeruginosa - Shan Su; Pengshuo Yin; Jing Li; Guanghui Chen; Yikun Wang; Di Qu; Zhoupeng Li; Xiaoyan Xue; Xiaoxing Luo; Mingkai Li (Elsevier, 2020)
Background: The development of bacterial biofilm can cause severe chronic infections and antibiotic resistance. Therefore, it poses a significant threat to public health. Staphylococcus aureus (S. aureus) and Pseudomonas aeruginosa (P. aeruginosa) are two major pathogens that can cause biofilm-associated infections, which leads to the urgent necessity of developing new agents with biofilm-forming inhibitory ability. Methods: A series of pyran derivatives were synthesized and characterized, and their in vitro anti-biofilm activity against S. aureus and P. aeruginosa were measured by minimal biofilm inhibitory concentration assay and FITC dye staining. The in vivo antibiofilm therapeutical effects were evaluated in S. aureus induced tissue cage infection mice model and P. aeruginosa induced urinary tract catheter infection rat model. Results: Several pyran derivatives showed the in vitro anti-biofilm activity against S. aureus and P. aeruginosa, and the activity of these compounds was not mediated through the accessory gene regulator (agr) quorum sensing system of S. aureus. One of these pyran derivatives, namely 2-amino-4-(2,6-dichlorophenyl)-3-cyano-5-oxo-4H,5H-pyrano[3,2c]chromene, exhibited significant inhibitory biofilm-formation activity in S. aureus tissue cage infection mice model and in the P. aeruginosa-infected urinary tract catheters of experimental rats. Conclusions: The data indicated that this pyran derivative is a possible lead compound that can be used for the development of novel anti-biofilm agents against S. aureus and P. aeruginosa infection. Keywords: Staphylococcus aureus, Pseudomonas aeruginosa, Biofilm, Quorum sensing system, Pyran derivative